Towards a typological conception of the factors of ‎entrepreneurial failure: Case of small Algerian companies - Hamidi ‎Youcef ‎; Gheribi , Ahmed (Dirassat Journal Economic Issue, 2016)
The present article aims at extracting the types and the causes of failure that may face the small and medium companies. For this purpose, we used a double classification (pyramidal and non-pyramidal) of data basis consisting of 360 small companies in a state of bankrupt. The method of multi factor analysis allowed the extraction of three special types concerning the bankrupt and the withdrawal of those companies from the market in such a way that each type comes with a certain numbers of characteristics.